A bibliographical review about the participation of students from professional education in the evaluation of institutions and courses (Revista Brasileira Multidisciplinar, 2020)
The evaluation of institutions and courses is an essential action for improvement of educational establishments. Promoting the participation of students is the most meaningful way to obtain relevant information about this process. This study of systematic review of bibliography aimed at reviewing the national bibliography published from 2013 to 2018, about papers developed with students from technical and technological professional education from Federal Institutes of Education, Science and Technology. Thus, a survey was carried out in the database of Scientific Electronic Library Online (SciELO), Google Academic and in the Periodic Portal of CAPES. It was observed that the professional inclusion of the students tends to be the parameter most commonly used to evaluate institutions and courses, followed by satisfaction with the education received. By analyzing the results, it is inferred that the parameter used to assess institutions and courses focused only on professional inclusion. Despite its good results, this is insufficient, considering the existence of several factors which interfere in this process, regardless the institution acting. Regarding the satisfaction of the students with the education received, it is understood, in general, as a positive evaluation of institutions and courses.  As for the parameter of effectiveness of professional education and regional socioeconomic development, the authors highlighted how essential the role of education is in this process.  In sum, the evaluation of institutions and courses, from this perspective, is an important means to obtain necessary feedback to promote improvement actions of educational policies.